2020
DOI: 10.1007/s00392-020-01622-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, procedural and long-term outcome of ischemic VT ablation in patients with previous anterior versus inferior myocardial infarction

Abstract: Background Outcome of ischemic VT ablation may differ between patients with previous myocardial infarction (MI) in relation to infarct localization. Methods We analyzed procedural data, acute and long-term outcomes of 152 consecutive patients (139 men, mean age 67 ± 9 years) with previous anterior or inferior MI who underwent ischemic VT ablation at our institution between January 2010 and October 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Previous research shows that reperfusion and NR are the main reasons for the deterioration of the cells exposed to the ischemic environment ( Wang et al, 2020b ). At the same time, it also leads to the poor prognosis of patients with acute myocardial infarction, such as cardiac arrhythmia, heart failure, and cardiogenic shock ( Vrints, 2020 ; Wasmer et al, 2020 ). The factors associated with the establishment of NR include endothelial dysfunction, compression of capillaries by swollen myocytes, leukocyte adherence, microvascular ischemia, oxidative stress, and inflammation ( Heusch, 2019 ; Wang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that reperfusion and NR are the main reasons for the deterioration of the cells exposed to the ischemic environment ( Wang et al, 2020b ). At the same time, it also leads to the poor prognosis of patients with acute myocardial infarction, such as cardiac arrhythmia, heart failure, and cardiogenic shock ( Vrints, 2020 ; Wasmer et al, 2020 ). The factors associated with the establishment of NR include endothelial dysfunction, compression of capillaries by swollen myocytes, leukocyte adherence, microvascular ischemia, oxidative stress, and inflammation ( Heusch, 2019 ; Wang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent observational study of 152 consecutive patients with cCAD (43% with ES) undergoing VT ablation found no differences in the incidence of ES between patients after anterior and inferior AMI. 34 In patients with NICM, the overall extent of the electroanatomical scar was similar, but lateral LV endocardial scar was more frequently observed in ES patients than in non-ES patients. 32 …”
Section: Pathophysiological Aspectsmentioning
confidence: 82%
“…Besides optimal treatment of heart failure and concomitant conditions 2 , 3 , catheter ablation has become the gold standard to prevent recurring episodes 4 . Still, recurrences are sometimes seen, especially in patients with advanced stages of structural heart disease and heart failure 5 . Often a substrate-based ablation approach, targeting low-voltage areas and local abnormal ventricular activation (LAVA) is chosen, especially when mapping during active VT is hemodynamically not tolerated 6 .…”
Section: Introductionmentioning
confidence: 99%